2017
DOI: 10.11634/216796061706894
|View full text |Cite
|
Sign up to set email alerts
|

Harmonizing Modern Day Employee Engagement with the Sociological Theory of Symbolic Interactionism

Abstract: Employee Engagement (EE) spans over 30 years discourse within the practitioner and scientific domain, and have become a strategic imperative within organizations. However, due to the tumultuous history of inconsistencies in conceptualization, poor validation, and various discrepancies among scholars and practitioners, the construct has attracted interest across disciplines and industry. Accordingly, the claims of its positive impact on bottom line and other organizational outcome have become the catalyst for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…In fact, it has been found that due to the dynamic nature of EE, drivers of EE are constantly changing. Therefore what will engage an employee may change tomorrow (Simon & Zhou, 2017). Accordingly, this has led some researchers to conceptualize EE as a multi-dimensional construct (Crawford, 2014;Saks, 2006).…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it has been found that due to the dynamic nature of EE, drivers of EE are constantly changing. Therefore what will engage an employee may change tomorrow (Simon & Zhou, 2017). Accordingly, this has led some researchers to conceptualize EE as a multi-dimensional construct (Crawford, 2014;Saks, 2006).…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%
“…In fact, the number of studies on the drivers and outcome of EE are many (Macey & Schneider, 2008;Saks, 2006;Wollard & Shuck, 2011). However, the changing pace of the global workforce, and its subsequent impact of human behaviour have influenced the shifting of the metaphoric goal post of employee engagement, and employee engagement may fluctuate (Bakker, 2014), as EE is not consistent and the influencers means different things to different people (Simon & Zhou, 2017) . Nonetheless, corporate sustainability may provide another level of explanation on the other factors influencing EE which may contribute significantly to the broader knowledge on the concept as well as to an organization's competitive advantage.…”
Section: Employee Engagement As a Business Imperativementioning
confidence: 99%
“…Research findings and the various gaps in the employee engagement (EE) literature makes it both an enigmatic and interesting concept for further study. Employee Engagement by virtue of its dynamic nature means different things to different interest groups (Simon & Zhou, 2017). Owing to the positive characteristics of EE such as vigor, dedication and absorption (Schaufeli et al, 2002), EE has been strategized by many business leaders as a business imperative for sustaining competitive advantage (Shuck, Reio & Rocco, 2011).…”
Section: Human Resource Management Practices and Employee Engagementmentioning
confidence: 99%
“…Owing to the positive characteristics of EE such as vigor, dedication and absorption (Schaufeli et al, 2002), EE has been strategized by many business leaders as a business imperative for sustaining competitive advantage (Shuck, Reio & Rocco, 2011). Consistent with these overt manifestations of EE, organizations have recognized that EE can only come from an employee"s discretionary effort (Schaufeli, 2014;Simon & Zhou, 2017). Therefore, HRM strategies that support HRM practices that are believed to be drivers of EE are implemented to create an environment which will inspire and facilitate the desire for employees to become engaged.…”
Section: Human Resource Management Practices and Employee Engagementmentioning
confidence: 99%
See 1 more Smart Citation